2014
DOI: 10.1002/2013gl059095
|View full text |Cite
|
Sign up to set email alerts
|

How will orographic precipitation respond to surface warming? An idealized thermodynamic perspective

Abstract: Future changes in orographic precipitation will have important consequences for societies and ecosystems near mountain ranges. Here we use a simple numerical model to evaluate the response of orographic precipitation to surface warming under idealized conditions representative of the strongest orographic storms. We find an upward shift in the pattern of condensation with warming, caused by larger fractional changes in condensation at low temperature and amplified warming aloft. As a result, the distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 35 publications
7
69
0
Order By: Relevance
“…For warm cloud processes, the precipitation growth is dominated by the collision-coalescence process. However, as shown in both Kirshbaum and Smith (2008) and Siler and Roe (2014) the increase in condensation rate is less than the increase in atmospheric water vapor. In other words, the air needs to be lifted further up to reach condensation.…”
Section: Changes In the Vertical Structurementioning
confidence: 88%
See 2 more Smart Citations
“…For warm cloud processes, the precipitation growth is dominated by the collision-coalescence process. However, as shown in both Kirshbaum and Smith (2008) and Siler and Roe (2014) the increase in condensation rate is less than the increase in atmospheric water vapor. In other words, the air needs to be lifted further up to reach condensation.…”
Section: Changes In the Vertical Structurementioning
confidence: 88%
“…Allan and Ingram 2002;Trenberth et al 2003;Pall et al 2006;Loriaux et al 2013). By using a simple numerical model for idealized extreme storms, Siler and Roe (2014) found that orographic precipitation had a lower response to surface warming than expected by the CC-relation. They noted a decrease in the condensation rate combined with an increase in transport of precipitation to the lee side of the mountain, where evaporation occurs, as the main reasons Abstract Using high resolution convective permitting simulations, we have investigated the sensitivity of historical orographically enhanced extreme precipitation events to idealized temperature perturbations.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, we have not discussed the potential influence of the Pennine Mountains to the west of Sheffield in influencing precipitation by orographic enhancement. A warmer climate might result in a shift of precipitation downwind in orographic regions [47]. Many storms that cross the UK do so from the southwest, so this factor could enhance precipitation rates across WP and rain-shadow regions of the UK.…”
Section: Future Evolution Of Extremesmentioning
confidence: 99%
“…Fowler and Ekström, 2009;Herrera et al, 2010;Buishand, 2011, 2012;Rajczak et al, 2013;Bartholy et al, 2015;Danandeh Mehr and Kahya, 2016). Although growing attention has been given to studies at sub-daily timescales in recent years, the complexity of physical processes related to sub-daily extremes (Stocker et al, 2013;Siler and Roe, 2014) and their simplification within climate model parameterizations make assessment of simulated sub-daily precipitation challenging, particularly since its validation is impaired by the lack of long and high-quality observed rainfall data series at hourly or sub-hourly timescales with sufficient spatial coverage allowing for comparison to simulated (spatial average) rainfall (Westra et al, 2014).…”
Section: Introductionmentioning
confidence: 99%